Toll-Like Receptors and RIG-I-Like Receptors Play Important Roles in Resisting Flavivirus. (14th May 2018) - Guo, Hong-Yan; Zhang, Xing-Cui; Jia, Ren-Yong
Abstract : Flaviviridae family is a class of single-stranded RNA virus, which is fatal to human and animals and mainly prevalent in subtropic and tropic countries. Even though people and animals are barraged with flavivirus infection every year, we have not invented either vaccines or antiviral for most flavivirus infections yet. Innate immunity is the first line of defense in resisting pathogen invasion, serving an important role in a resisting virus. Toll-like receptors (TLRs) and retinoic acid-inducible gene I- (RIG-I-) like receptors (RLRs) are crucial pattern recognition receptors (PRRs) that play essential roles in recognizing and clearing pathogens, including resisting flavivirus. In the present review, we provide a significant reference for further research on the function of innate immunity in resisting flavivirus.